Priest movement onis: the church in Peru before social justice demands (1968-1975) - Ramírez Aguilar, Juan (2014)
The present research studies the historic process of a Peruvian Catholic Church sector: priest movement ONIS. The aforementioned movement published pronouncements and declarations from the social doctrine of the church, expressing common characteristics of the time: fight against poverty and the preferential option for the poor. The structure of the research is a stage post-II Vatican Council, Latin American Priest Movements and finally, ONIS: doctrine of the Church and praxis. In this manner,  the purpose of this research is to show that Priest Movement ONIS made known a pastoral work of the popular sectors oriented to social justice.